The Use of Crossword Puzzle Game to Improve Vocabulary Mastery at SMPN 05 Padang for VII Grade - Rezqi Surya Vendri (Lesson Journal: Languange, Applied Linguistics, and Education Journal, 2020)
This aim of this study is at improving the vocabulary mastery through the use of crossword puzzles among seventh grade students of SMPN 05 Padang in the academic year 2019/2020. This research will use the interactive method by apply the crossword puzzle and, use the Kemmis and McTaggart models. The population of this research will be targeting the students of the class 7-7 at SMPN 5 Padang. The data get from the pre test and post test. After getting the data the researcher will be using the statically technique of standard deviation and t-test for get the significant difference